Research of CamShift Algorithm to Track Motion Objects - Li Zhu; Tao Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
At present, objects detection, identification and tracking are the very popular research areas in computing vision. A real-time objects tracking system was proposed in this paper. This paper focuses on improve CamShift algorithm, which can track the motion objects with high a accuracy. An Adaptive Gaussian Background Model is proposed in the system , which was established in order to automatically update the background and detect the outline of moving objects. By analyzing different algorithms, this paper brings out approaches to promote the performance.The CamShift algorithm to complete motion detection and objects tracking, which applied for static background video sequences. And the experimental results show that this algorithm can detect all motion objects and track almost motion objects. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3037